Asignación de recursos públicos en la Universidad Nacional de la Amazonía Peruana, periodo 2018 – 2022 - Navarrro Huaman, Dafna María (2024)
The allocation of public resources are actions that are mainly aimed at transferring funds to public sector entities and institutions so that they can have the necessary means and ensure the development of programmed activities in order to be able to meet its objectives and goals. The study includes the conduct of a survey on the "Allocation of Public Resources at the National University of the Peruvian Amazon, period 2018 - 2022", focusing basically on determining the evolution of these resources in the period evaluated. Its development implied the use of a methodology of a quantitative approach, of descriptive level and non-experimental design, whose scope was a period of five (5) years; in addition, several techniques had to be used such as selective review, analysis, tabulation, calculation, and the collection of effectual data through the record sheet. The results obtained reveal essentially a fluctuating evolution in the allocation of public resources, due to a constant variation in them.